Analysis of energy consumption in pineapple cultivation on peat soil: a case study at Kuala Rompin Pahang, Malaysia / Mohamad Hafizi Mohamed Samim - Mohamed Samim, Mohamad Hafizi (Faculty of Plantation and Agrotechnology, 2019)
The study was conducted to calculate energy consumption of pineapple cultivation for 10 acres area. Every stage pineapple production was analyzed its use of energy such as land preparation, planting, weeding, fertilizing, spraying hormone and harvesting on peat soil in Malaysia. The study also aimed to identify the relationship between input and output energy in pineapple production. Data were collected based on direct field observations at a pineapple plantation under the management of small farmers at Kampung Tanam, Kuala Rompin Pahang, Malaysia. Besides, the data also has been taken through oral interviewed to gather any relevant information that can be used in this study. The highest energy input used in pineapple production on peat soil is fertilizer which is 59.95% from total energy equivalents used in the production. Fuel is the second highest with 21.24% from total energy equivalents followed by suckers, agrochemical, labor and machine at 9.23%, 4.55%, 3.15%, and 1.88% respectively. The ratio of energy output/input in this production was 4.68. It means that the energy input is effectively used in the pineapple production on peat soil since the energy output/input ratio is greater than 1. Machinery give a huge impact on any production especially on pineapple production because there are a lot of job can be done easily using machinery. Besides, farm’s capability to do work more efficiently and can reduce labor shortage problem.